Oxidative Stress and Pathogenesis in Malaria - Vasquez, Marilyn; Zuniga, Marisol; Rodriguez, Ana (Frontiers in Cellular and Infection Microbiology, 2021)
Malaria is a highly inflammatory and oxidative disease. The production of reactive oxygen species by host phagocytes is an essential component of the host response to Plasmodium infection. Moreover, host oxidative enzymes, such as xanthine oxidase, are upregulated in malaria patients. Although increased production of reactive oxygen species contributes to the clearance of the parasite, excessive amounts of these free radicals can mediate inflammation and cause extensive damage to host cells and tissues, probably contributing to severe pathologies. Plasmodium has a variety of antioxidant enzymes that allow it to survive amidst this oxidative onslaught. However, parasitic degradation of hemoglobin within the infected red blood cell generates free heme, which is released at the end of the replication cycle, further aggravating the oxidative burden on the host and possibly contributing to the severity of life-threatening malarial complications. Additionally, the highly inflammatory response to malaria contributes to exacerbate the oxidative response. In this review, we discuss host and parasite-derived sources of oxidative stress that may promote severe disease in P. falciparum infection. Therapeutics that restore and maintain oxidative balance in malaria patients may be useful in preventing lethal complications of this disease.